2015
DOI: 10.1038/ncomms8227
|View full text |Cite
|
Sign up to set email alerts
|

A chemogenomic screening identifies CK2 as a target for pro-senescence therapy in PTEN-deficient tumours

Abstract: Enhancement of cellular senescence in tumours triggers a stable cell growth arrest and activation of an antitumour immune response that can be exploited for cancer therapy. Currently, there are only a limited number of targeted therapies that act by increasing senescence in cancers, but the majority of them are not selective and also target healthy cells. Here we developed a chemogenomic screening to identify compounds that enhance senescence in PTEN-deficient cells without affecting normal cells. By using thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Among these, PDK1 and CK2 showed increased activity in high cytokine producing IGROV-1 cells compared with its TNF network inhibited form (shCXCR4 cells). Since PDK1 and CK2 are involved in the regulation of the PI3K/AKT pathway, we have confirmed these findings by visualizing the phosphorylation of PDK1 and the CK2 specific phosphorylation of AKT (Ser129), a phosphorylation site that is often used as a marker of CK2 activity by Western blot analysis (Figure 1C ) [ 29 , 30 ]. Phosphorylation of PDK1 (Ser241), PI3K (Tyr458), AKT (Ser473 and Ser129), were reduced in the shCXCR4 cells in which the TNF network has been inhibited.…”
Section: Resultssupporting
confidence: 65%
“…Among these, PDK1 and CK2 showed increased activity in high cytokine producing IGROV-1 cells compared with its TNF network inhibited form (shCXCR4 cells). Since PDK1 and CK2 are involved in the regulation of the PI3K/AKT pathway, we have confirmed these findings by visualizing the phosphorylation of PDK1 and the CK2 specific phosphorylation of AKT (Ser129), a phosphorylation site that is often used as a marker of CK2 activity by Western blot analysis (Figure 1C ) [ 29 , 30 ]. Phosphorylation of PDK1 (Ser241), PI3K (Tyr458), AKT (Ser473 and Ser129), were reduced in the shCXCR4 cells in which the TNF network has been inhibited.…”
Section: Resultssupporting
confidence: 65%
“…Given these premises, it is not surprising that quinalizarin is effective in many disease models in which CK2 is effectively implicated, thus confirming CK2 as the principal target of this molecule. Recently quinalizarin has provided a strong argument to support the concept that CK2 may represent an appealing target for prosenescence antitumor strategies [ 28 ]. From a molecular point of view a detailed crystallographic study of the binding mode between quinalizarin and CK2 α subunit has been performed; initially cocrystallyzed with Zea Mays CK2 at pH 7.5 (PDB code: 3FL5 [ 10 ]), later the complex between quinalizarin and human CK2 was solved at pH 6.5 and 8.5 (PDB codes: 3Q9Z and 3Q9Y, resp.…”
Section: Introductionmentioning
confidence: 99%
“…ERK5/CKII is involved in GPIb-IX-mediated platelet activation via regulation of the PTEN/PI3K/Akt pathway CKII is composed of two a subunits and two b subunits, and it phosphorylates serine/threonine/tyrosine of its substrate [26,27]. It has been reported that CKII can phosphorylate and attenuate the activity of phosphatase and tensin homolog deleted on chromosome ten (PTEN) [28]. Whether ERK5/CKII was involved in GPIb-IX-mediated platelet activation through regulation of PTEN phosphorylation requires investigation.…”
Section: Ckii Is One Of Erk5-associated Proteinsmentioning
confidence: 99%